Immune functions of avian erythrocytes: a comprehensive review from basic biology to pathogen-induced responses - Cai, Fujuan; Wang, Yuzhen (Frontiers in Immunology, 2025)
Avian erythrocytes, traditionally perceived as mere oxygen transporters, are increasingly acknowledged as integral components of the immune system. Unlike enucleated erythrocytes of mammals, avian erythrocytes retain functional nuclei and organelles, allowing them to produce immune molecules like cytokines and antimicrobial peptides essential for pathogen recognition and clearance. This review provides a comprehensive elucidation of the molecular mechanisms underpinning the immune functions of avian erythrocytes and their responses to infections induced by viruses, bacteria, fungi, mycoplasma, and parasites. Through a systematic analysis of literature spanning the past 16 years, we synthesize evidence regarding the involvement of avian erythrocytes in Toll-like receptor (TLR) signaling, oxidative stress responses, phagocytosis, immune adhesion, and apoptosis-mediated immune evasion. We further demonstrate their pivotal role in anti-infective immunity, underscoring their ability to synthesize and secrete immune molecules, effectively capture and eliminate pathogens, and precisely regulate inflammatory responses and immune homeostasis. Finally, we identify existing knowledge gaps and underscore the necessity for further research to fully elucidate erythrocyte-mediated immune mechanisms and their potential applications in the prevention and control of avian diseases.